2023
DOI: 10.1097/wco.0000000000001173
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in dementia with Lewy bodies: the evolving concept of co-pathologies, patient selection and biomarkers

Abstract: Purpose of review Currently, no disease modifying therapies (DMTs) have been approved for use in dementia with Lewy bodies (DLB). Clinical trials face difficulties due to the clinical and neuropathological heterogeneity of the condition with a diverse array of neuropathogenic mechanisms contributing to the clinical phenotype. The purpose of this review is to describe how recent advances in the development of biofluid biomarkers may be used in clinical trials to tackle some of these challenges. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…This information can help guide clinical care and provide valuable insights for patients and their caregivers. Moreover, the potential use of plasma pTau181 in LBD drug development is promising, as it may facilitate the enrichment of clinical trials with participants more likely to progress, allow for stratification based on the presence or absence of concomitant ADNC or amyloidosis, and may enable the detection of treatment response 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…This information can help guide clinical care and provide valuable insights for patients and their caregivers. Moreover, the potential use of plasma pTau181 in LBD drug development is promising, as it may facilitate the enrichment of clinical trials with participants more likely to progress, allow for stratification based on the presence or absence of concomitant ADNC or amyloidosis, and may enable the detection of treatment response 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…qLRP was able to distinguish with some certainty AD from DLB, which is an important differential diagnostic to AD, as DLB shows a high degree of co‐pathology and shares symptoms with AD. 31 , 32 Previous studies showed that Parkinson's disease, which shares neuropathological features with DLB, could be distinguished from HCs using qLRP, 33 but no studies have to our knowledge investigated the potential of qLRP in distinguishing AD and DLB. The mechanism that drives the diagnostic ability of qLRP for this discrimination is not known in detail, but autonomic dysfunction could be hypothesized to play a role as the light reflex is under the influence of the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies are also targeting amyloid and tau simultaneously. Thirteen treatments are under investigation for dementia with Lewy bodies . Current investigational medications for frontotemporal degeneration have been focused on people with identifiable genetic variations ( GRN , C9ORF72 ), as well as on various mechanisms to suppress expression and pathological dysregulation of tau and progranulin pathways …”
Section: Disease Treatmentmentioning
confidence: 99%